Glass powder, silver-aluminum paste containing glass powder and N-type solar cell prepared from silver-aluminum paste
By simultaneously adding rare earth metal oxides and zinc oxide to the glass powder, the contact problems caused by the flow of glass powder at high temperatures and the crystallization problems caused by the rare earth metal oxides are solved, and better electrode contact with silicon and lower flow temperatures are achieved.
Patent Information
- Application Number
- CN202311230054.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the flow of glass powder at high temperature causes the passivation film to open, affecting the contact between the electrode and silicon, and the presence of rare earth metal oxides will lead to crystallization of the glass and reduce fluidity. Meanwhile, the glass powder has fluidity at lower temperatures to open the passivation film early, improving the contact quality between the electrode and silicon.
While adding rare earth metal oxide to the glass powder, an appropriate amount of zinc oxide is added to improve the fluidity of the glass powder and enhance the contact between the electrode and silicon.
By adding zinc oxide, the fluidity of the glass powder and the contact quality between the electrode and silicon are improved, while the flow temperature is reduced, and the glass crystallization problem caused by rare earth metal oxides is solved.
Smart Images

Figure BDA0004463577900000151
Abstract
Description
Technical Field
[0001] The invention relates to a glass powder, a silver-aluminum paste for preparing an N-type solar cell comprising the glass powder, and an N-type solar cell prepared by the silver-aluminum paste.
[0002] The present invention further relates to a method for preparing the glass powder, silver aluminum paste and N-type solar cell. Background Art
[0003] Solar cells are devices that convert light energy from the sun into electrical energy. Light irradiates the silicon wafer of the substrate, generating electrons and holes, which are guided through electrodes located on the front side (i.e. the side irradiated by light) and the back side (i.e. the side not irradiated by light) of the substrate, thereby forming an electric current to obtain electrical energy. The electrodes in contact with the silicon wafer in the solar cell are usually manufactured by applying a conductive paste to the silicon wafer by screen printing and then sintering the conductive paste.
[0004] The glass powder in the silver-aluminum paste used to prepare N-type solar cells flows down at high temperatures, thereby opening the passivation film and allowing the sintered electrode to form contact with silicon. Currently, solar cells are increasingly inclined to use ultra-fine wires, and under this trend, the requirements for contact are becoming higher and higher.
[0005] In order to obtain better contact, rare earth metal oxides are added to glass powder in the prior art to increase the impurity energy level in silicon and enhance the contact between the electrode and silicon.
[0006] For example, WO2022 / 116646A1 discloses a glass powder containing lanthanide oxides, and an electrode paste containing lanthanum aluminum alloy formed therefrom. The invention increases the impurity energy level in silicon by adding lanthanide elements to the electrode paste, thereby enhancing the contact between the electrode paste and the emitter. At the same time, the lanthanum aluminum alloy added to the electrode paste forms effective aluminum doping, reduces metal recombination at the contact position, and balances ohmic contact and metal recombination.
[0007] However, the presence of rare earth metal oxides in glass powder will promote the crystallization of glass, resulting in poor fluidity and affecting contact. There is a need in the art to eliminate the above problems caused by adding rare earth metal oxides to glass powder.
[0008] In addition, regardless of whether rare earth metal oxides are present in the glass powder, the art also hopes that the glass powder has fluidity at a lower temperature, so as to open the passivation film earlier and make the contact between the electrode and silicon better.
[0009]
[0006] Therefore, there is a need in the art for a glass frit having enhanced electrode-to-silicon contact and reduced flow temperature, especially when the glass frit contains rare earth metal oxides. SUMMARY OF THE INVENTION
[0011] The invention improves the fluidity of the glass powder and strengthens the contact between the electrode and silicon by adding zinc oxide of appropriate content to the glass powder while adding rare earth metal oxide to the glass powder.
[0012] The present invention relates to a glass powder composition, wherein the glass powder composition comprises 14-30 mol %, preferably 15-20 mol %, more preferably 15-17 mol % of zinc oxide, and one or more of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate, based on the total amount of metal oxides in the glass powder composition.
[0013] The present invention further relates to such a glass powder composition, which further comprises a rare earth metal oxide selected from the group consisting of lanthanum oxide, yttrium oxide, ytterbium oxide, scandium oxide, europium oxide, gadolinium oxide and combinations thereof, preferably gadolinium oxide.
[0014] The present invention further relates to a glass powder composition, wherein the content of the rare earth metal oxide in the glass powder composition is 1-10 mol %, preferably 1-5 mol %, more preferably 1-3 mol %, based on the total amount of metal oxides in the glass powder composition.
[0015] The present invention further relates to a glass powder composition, wherein the contents of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate in the glass powder composition are respectively
[0016] Lead oxide: 20-60 mol%, preferably 40-50 mol%,
[0017] Silicon oxide: 2-20 mol%, preferably 5-15 mol%,
[0018] Boron oxide: 10-30 mol%, preferably 15-25 mol%,
[0019] Aluminum oxide: 0-5 mol%, preferably 0.5-3 mol%, and / or
[0020] Calcium carbonate: 1-10 mol %, preferably 2-8 mol %.
[0021] The present invention also relates to a glass powder obtained from the glass powder composition of the present invention, wherein the particle size D50 is 0.1-5 μm, preferably 0.2-3 μm, more preferably 0.5-2 μm.
[0022] The present invention further relates to a glass powder having a glass transition temperature of 380-390°C.
[0023] The present invention further relates to a glass powder having a flow temperature of 540-570°C.
[0024] The present invention also relates to a silver-aluminum paste, which contains the glass powder of the present invention.
[0025] The present invention further relates to a silver-aluminum paste in which the content of the glass powder of the present invention is 2-15 wt %, preferably 2.2-10 wt %, and more preferably 2.5-8 wt %, based on the total amount of the silver-aluminum paste.
[0026] The present invention also relates to an N-type solar cell, which comprises an electrode prepared from the silver-aluminum paste of the present invention.
[0027] The present invention relates to the use of zinc oxide for improving the contact between an N-type solar cell electrode and silicon, and / or improving the fluidity of a glass powder, wherein 14-30 mol %, preferably 15-20 mol %, more preferably 15-17 mol % of zinc oxide is added to a glass powder composition for preparing the glass powder, based on the total amount of metal oxides in the glass powder composition, the glass powder composition comprises one or more of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate, and the glass powder is contained in a silver aluminum paste for preparing the N-type solar cell electrode.
[0028] The present invention further includes the use of such zinc oxide, wherein the glass powder composition further comprises a rare earth metal oxide, and the rare earth metal oxide is selected from lanthanum oxide, yttrium oxide, ytterbium oxide, scandium oxide, europium oxide, gadolinium oxide and combinations thereof, preferably gadolinium oxide; wherein based on the total amount of metal oxides in the glass powder composition, the content of the rare earth metal oxide in the glass powder composition is preferably 1-10 mol %, more preferably 1-5 mol %, and most preferably 1-3 mol %. Specific implementation plan
[0029] Glass powder
[0030] The invention relates to a glass powder and a preparation method thereof. The glass powder is prepared from the glass powder composition of the invention and can be used to prepare silver-aluminum paste used in N-type solar cells.
[0031] In one embodiment of the present invention, the glass powder composition of the present invention comprises 14-30 mol %, preferably 15-20 mol %, more preferably 15-17 mol % of zinc oxide.
[0032] In one embodiment of the present invention, the glass frit composition of the present invention comprises rare earth metal oxides and zinc oxide, and metal oxides commonly used in the art in amounts commonly used in the art.
[0033] In one embodiment of the present invention, the glass powder composition of the present invention comprises a rare earth metal oxide selected from lanthanum oxide, yttrium oxide, cerium oxide, ytterbium oxide, scandium oxide, europium oxide, gadolinium oxide and combinations thereof, preferably gadolinium oxide.
[0034] The glass powder composition of the present invention preferably comprises 1-10 mol %, more preferably 1-5 mol %, most preferably 1-3 mol % of rare earth metal oxide.
[0035] The glass powder composition of the present invention further comprises other components of the glass powder composition commonly used in the art for preparing silver-aluminum paste for N-type solar cells, and the amounts thereof are the amounts commonly used in the art.
[0036] In one embodiment of the present invention, the glass powder composition of the present invention comprises, by mole, 20-60 mol %, preferably 40-50 mol %, lead oxide, 2-20 mol %, preferably 5-15 mol %, silicon oxide, 10-30 mol %, preferably 15-25 mol %, boron oxide, 0-5 mol %, preferably 0.5-3 mol %, aluminum oxide, and / or 1-10 mol %, preferably 2-8 mol %, calcium carbonate.
[0037] The glass powder of the present invention can be obtained from the above-mentioned glass powder composition by a preparation method known to those skilled in the art.
[0038] In one embodiment of the present invention, the glass powder of the present invention is prepared by the following method: uniformly mixing the components of the glass powder composition of the present invention, melting the mixture to obtain glass, preferably quenching in deionized water, and finally making the product into particles with a desired particle size.
[0039] Preferably, the glass powder is prepared by the following method: the components are mixed uniformly, the mixture is charged into a crucible, the crucible is placed in a muffle furnace and the mixture is melted at a high temperature, then the molten glass is removed from the muffle furnace and poured into a bucket filled with deionized water for water quenching, and the quenched glass slag is ground with a ball mill to obtain a powder with a desired D50.
[0040] In the above method, the temperature of the muffle furnace is high enough to melt the components of the glass powder composition of the present invention, and the melting time is long enough to uniformly mix the components.
[0041] More preferably, in the preparation of the glass powder of the present invention, the temperature of the muffle furnace is 800-1500° C., preferably 900-1200° C., and the melting time of the mixture is 15 minutes to 2 hours, preferably 30 minutes to 1 hour.
[0042] The glass powder of the present invention has a particle size generally used in the art.
[0043] Particle size is a particle property known to those skilled in the art. Particle size D50 is the median particle size or median value of the particle size distribution, which is the particle size value at the 50% position in the cumulative distribution. Particle size and its distribution can be measured via laser diffraction, dynamic light scattering, imaging, electrophoretic light scattering, or any other method known in the art.
[0044] In one embodiment of the present invention, the glass powder of the present invention has a particle size D50 of 0.1-5 μm, for example 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm, preferably 0.2-3 μm or 0.5-2 μm.
[0045] In a preferred embodiment of the present invention, the glass powder of the present invention has a glass transition temperature of 380-390°C.
[0046] In another preferred embodiment of the present invention, the glass powder of the present invention has a flow temperature of 540-570°C.
[0047] Silver Aluminum Paste
[0048] The present invention further relates to a silver-aluminum paste containing the glass powder and a preparation method thereof. The silver-aluminum paste can be used to prepare an N-type solar cell.
[0049] In one embodiment of the present invention, the silver-aluminum paste of the present invention comprises silver powder and aluminum powder, the glass powder of the present invention, an organic vehicle, and additives.
[0050] The silver-aluminum paste of the present invention comprises silver powder and aluminum powder which are commonly used in the art to prepare the silver-aluminum paste for N-type solar cells.
[0051] In one embodiment of the present invention, the silver-aluminum paste of the present invention may contain 75-92 wt %, preferably 78-91 wt %, more preferably 80-90 wt % of silver powder, based on the total weight of the silver-aluminum paste.
[0052] In one embodiment of the present invention, the silver aluminum paste of the present invention may contain 0.6-5 wt %, preferably 0.7-4.5 wt % or 0.8-4 wt % or 1-3 wt % aluminum powder, based on the total weight of the silver aluminum paste.
[0053] In one embodiment of the present invention, the particle size D50 of the silver powder and the aluminum powder may be 0.1-3 μm, preferably 0.1-1.5 μm or 0.1-1 μm.
[0054] The silver-aluminum paste of the present invention contains the glass powder of the present invention.
[0055] In one embodiment of the present invention, the silver aluminum paste of the present invention contains 2-15 wt %, preferably 2.2-10 wt %, more preferably 2.5-8 wt % of the glass powder according to the present invention.
[0056] In one embodiment of the present invention, the silver-aluminum paste of the present invention comprises an organic vehicle commonly used in the art, which is a solution, emulsion or dispersant based on one or more solvents, preferably an organic solvent, which ensures that the components of the silver-aluminum paste are present in a dissolved, emulsified or dispersed form. The preferred organic vehicle is an organic vehicle that provides the best stability of the components within the silver-aluminum paste and imparts viscosity to the silver-aluminum paste that allows effective printability.
[0057] In one embodiment, the amount of the organic vehicle may be 2-20 wt %, more preferably 3-15 wt %, most preferably 5-10 wt %, based on the total weight of the silver aluminum paste.
[0058] In one embodiment, the organic vehicle comprises an organic solvent, a binder (eg, a polymer, a resin), a surfactant, or an additive, or any combination thereof. For example, in one embodiment, the organic vehicle comprises one or more binders in an organic solvent.
[0059] The binder may be present in an amount of 0.1-10 wt %, preferably 0.1-8 wt %, more preferably 0.5-7 wt %, based on the total weight of the organic vehicle. Preferred binders in the present invention are binders that promote the formation of silver aluminum pastes with favorable stability, printability, viscosity and sintering properties. Preferred binders according to the present invention (which generally belong to the category referred to as "resins") are polymeric binders, monomeric binders and binders that are a combination of polymers and monomers. The polymeric binder may also be a copolymer.
[0060] Preferred polymeric binders include binders carrying functional groups in the polymer backbone, binders carrying functional groups outside the backbone, and binders carrying functional groups inside and outside the backbone. Preferred polymers carrying functional groups in the backbone include, for example, polyesters, substituted polyesters, polycarbonates, substituted polycarbonates, polymers carrying cyclic groups in the backbone, polysaccharides, substituted polysaccharides, polyurethanes, substituted polyurethanes, polyamides, substituted polyamides, phenolic resins, substituted phenolic resins, copolymers of one or more monomers of the above polymers (optionally with other comonomers) or combinations of at least two thereof.
[0061] Preferred polymers carrying cyclic groups in the main chain include, for example, polyvinyl butyral (PVB) and its derivatives and polyterpineol and its derivatives or mixtures thereof. Preferred polysaccharides include, for example, ethyl cellulose, cellulose and its alkyl derivatives, methyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, butyl cellulose, its derivatives and mixtures of at least two thereof. Other preferred polymers include, for example, cellulose ester resins, such as cellulose acetate propionate, cellulose acetate butyrate and any combination thereof. Other preferred polymers are those disclosed in U.S. Patent Application Publication No. 2013 / 0180583, which is incorporated herein by reference.
[0062] Preferred polymers carrying functional groups outside the polymer backbone are polymers carrying amide groups, polymers carrying acid and / or ester groups (commonly referred to as acrylic resins) or polymers carrying a combination of the above functional groups or combinations thereof. Preferred polymers carrying amide groups outside the backbone include, for example, polyvinyl pyrrolidone (PVP) and its derivatives. Preferred polymers carrying acid and / or ester groups outside the backbone include, for example, polyacrylic acid and its derivatives, polymethyl methacrylate (PMMA) and its derivatives or mixtures thereof.
[0063] Preferred monomeric binders according to the present invention include, for example, monomeric binders based on ethylene glycol. Preferred monomeric binders based on ethylene glycol are binders having multiple ether groups, multiple ester groups, or binders having one ether group and one ester group, preferably the ether groups are methyl, ethyl, propyl, butyl, pentyl, hexyl and higher alkyl ethers, preferably the ester groups are acetates and their alkyl ether derivatives, preferably ethylene glycol monobutyl ether monoacetate or mixtures thereof.
[0064] Preferred binders in the present invention are, for example, alkyl cellulose (preferably ethyl cellulose), derivatives thereof, and mixtures thereof with other binders from the previous binder list, and the like.
[0065] The amount of the organic solvent may be 40 to 90% by weight, more preferably 35 to 85% by weight, based on the total weight of the organic vehicle.
[0066] Preferred solvents according to the present invention are solvents that allow the formation of silver-aluminum pastes with favorable viscosity, printability, stability and sintering properties. All solvents known in the art and considered suitable in the present invention can be used as solvents in the organic vehicle. According to the present invention, preferred solvents are solvents that allow a preferred high level of printability of the silver-aluminum paste as described above to be achieved. Preferred solvents according to the present invention are solvents that exist in liquid form at standard ambient temperature and pressure (SATP) (298.15K, 100kPa), preferably solvents having a boiling point above about 90°C and a melting point above about -20°C.
[0067] Preferred solvents according to the invention are polar or nonpolar, protic or aprotic, aromatic or nonaromatic. Preferred solvents according to the invention include, for example, monoalcohols, diols, polyalcohols, monoesters, diesters, polyesters, monoethers, diethers, polyethers, solvents comprising at least one or more of these classes of functional groups, optionally comprising other classes of functional groups, preferably cyclic groups, aromatic groups, unsaturated bonds, alcohol groups having one or more O atoms substituted by heteroatoms, ether groups having one or more O atoms substituted by heteroatoms, ester groups having one or more O atoms substituted by heteroatoms, and mixtures of two or more of the above solvents.
[0068] The organic vehicle may further include a surfactant and / or an additive. The amount of the surfactant may be 0-10% by weight, preferably 0-8% by weight, more preferably about 0.01-6% by weight, based on the gross weight of the organic vehicle. Preferred surfactants in the present invention are surfactants that promote the formation of silver-aluminum pastes with favorable stability, printability, viscosity and sintering properties. All surfactants known in the art and considered to be applicable in the present invention may be used as surfactants in the organic vehicle. Preferred surfactants are single-chain, double-chain or poly-chain. Preferred surfactants according to the present invention may have nonionic, anionic, cationic, amphoteric or zwitterionic heads. Preferred surfactants are polymeric and monomeric or mixtures thereof.
[0069] Preferred additives in the organic vehicle are those additives that are different from the above-mentioned vehicle components and promote the favorable properties of the silver aluminum paste (such as favorable viscosity and adhesion to the underlying substrate). Additives known in the art and considered suitable for use in the present invention can be used as additives in the organic vehicle. Preferred additives according to the present invention are thixotropic agents, viscosity modifiers, stabilizers, inorganic additives, thickeners, emulsifiers, dispersants, slip agents or pH modifiers and any combination thereof. Preferred thixotropic agents herein are carboxylic acid derivatives, preferably fatty acid derivatives or combinations thereof. Preferred fatty acid derivatives are C9H 19 COOH (decanoic acid), C 11 H 23 COOH (lauric acid), C 13 H 27 COOH (myristic acid), C 15 H 31 COOH (palmitic acid), C 17 H 35 COOH(stearic acid), C 18 H 34 O2(oleic acid), C 18 H 32 O2 (linoleic acid) or a combination thereof. A preferred combination of fatty acids in this context is castor oil.
[0070] In one embodiment of the present invention, the silver-aluminum paste of the present invention optionally contains additives commonly used in the art. Preferred additives are components added to the silver-aluminum paste in addition to the ingredients already explicitly mentioned, which are used to promote higher performance of the silver-aluminum paste, the electrodes made therefrom, or the resulting solar cells. All additives known in the art and considered suitable in the present invention can be used as additives in the silver-aluminum paste. In addition to the additives present in the glass powder and in the carrier, additives may also be present in the silver-aluminum paste. Preferred additives according to the present invention are thixotropic agents, viscosity regulators, emulsifiers, stabilizers or pH regulators, inorganic additives (such as silicon powder), thickeners and dispersants or a combination of at least two thereof, and inorganic additives are most preferred. Preferred inorganic additives according to the present invention are Mg, Ni, Te, W, Zn, Mg, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu and Cr or a combination of at least two thereof, preferably Zn, Sb, Mn, Ni, W, Te and Ru or a combination of at least two thereof, their oxides, compounds that can produce said metal oxides when fired, or mixtures of at least two of the above metals, mixtures of at least two of the above oxides, mixtures of at least two of the above compounds that can produce said metal oxides when fired, or mixtures of two or more of any of the above materials. The amount of the inorganic additive may be 0-1 wt % (e.g., 0.1 wt %, 0.5 wt % or 0.8 wt %), based on the total weight of the silver aluminum paste.
[0071] In one embodiment of the present invention, to form a silver aluminum paste, glass powder can be combined with silver powder and aluminum powder and an organic vehicle and optional additives using any method known in the art for preparing a paste. The preparation method is not critical as long as it produces a homogeneously dispersed paste. The components can be mixed, such as with a mixer, and then passed through a three-roll mill, for example, to make a dispersed, uniform paste.
[0072] Solar Cells
[0073] The present invention further relates to a solar cell, in particular an N-type solar cell, which comprises a substrate and an electrode formed by sintering the silver-aluminum paste of the present invention and bonded to the substrate.
[0074] Preferred solar cells are those with high efficiency in terms of the ratio of the total energy of incident light converted to electrical energy output. Lightweight and durable solar cells are also preferred. The solar cell comprises at least: (i) a front electrode, (ii) a front doped layer, (iii) a pn junction boundary, (iv) a back doped layer and (v) a back electrode and (vi) a passivation layer. The solar cell may also include additional layers for chemical / mechanical protection.
[0075] The solar cell substrate of the present invention may be a substrate for solar cells known to those skilled in the art.
[0076] The solar cell of the present invention has an electrode formed by sintering the silver-aluminum paste of the present invention and bonded to the substrate.
[0077] The printed electrode can be formed by applying the silver aluminum paste of the present invention to a substrate, such as a semiconductor substrate (such as a silicon wafer). The silver aluminum paste can be applied in any manner known in the art and considered suitable in the present invention. Examples include, but are not limited to, dipping, impregnation, pouring, dripping, injection, spraying, blade coating, flow coating, brushing or printing or a combination of at least two thereof. Preferably, the printing technique is inkjet printing, screen printing, flexographic printing, offset printing, relief printing or stencil printing or a combination of at least two thereof. It is preferred according to the present invention to apply the silver aluminum paste by printing, preferably by screen printing.
[0078] Firing is required to sinter the printed electrodes to form a solid conductor. Firing is well known in the art and may be achieved in any manner deemed appropriate in the present invention. It is preferred that firing is performed above the Tg of the glass frit material.
[0079] Outside the area occupied by the electrodes, the substrate of the present invention, preferably a silicon wafer, has an area where light can be efficiently absorbed to generate electron-hole pairs and efficiently separate holes and electrons across a boundary, preferably a pn junction boundary.
[0080] The pn junction boundary is located where the front doped layer of the wafer meets the back doped layer. In an n-type solar cell, the back doped layer is doped with an n-type dopant and the front doped layer is doped with a p-type dopant. In a p-type solar cell, the back doped layer is doped with a p-type dopant and the front doped layer is doped with an n-type dopant. According to a preferred embodiment of the present invention, a wafer having a pn junction boundary is prepared by first providing a doped silicon substrate and then applying a doped layer of the opposite type to one face of the substrate.
[0081] The above-mentioned dopants are preferably dopants that form pn junction boundaries by introducing electrons or holes into the band structure when added to the silicon wafer. According to the present invention, it is preferred to specifically select the types and concentrations of these dopants to adjust the band structure profile of the pn junction and set the light absorptivity and conductivity profile as required. The preferred p-type dopant according to the present invention is a dopant that adds holes to the band structure of the silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as p-type dopants. The preferred p-type dopant according to the present invention is a trivalent element, especially a trivalent element of Group 13 in the periodic table. The preferred Group 13 elements in the periodic table herein include, but are not limited to, boron, aluminum, gallium, indium, thallium or a combination of at least two thereof, wherein boron is particularly preferred.
[0082] Preferred n-type dopants according to the present invention are dopants that add electrons to the band structure of the silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as n-type dopants. Preferred n-type dopants according to the present invention are elements of the fifth group of the periodic table. Preferred elements of the fifth group of the periodic table herein include nitrogen, phosphorus, arsenic, antimony, bismuth or a combination of at least two thereof, wherein phosphorus is particularly preferred.
[0083] According to the present invention, an antireflection layer can be applied as an outer layer before the electrode is applied to the front side of the solar cell. The preferred antireflection layer according to the present invention is an antireflection layer that reduces the proportion of incident light reflected by the front side and increases the proportion of incident light that will be absorbed by the wafer across the front side. Antireflection layers that produce a favorable absorption ratio / reflection ratio are susceptible to silver aluminum paste etching. In addition, antireflection layers that are resistant to the temperatures required for firing the silver aluminum paste and do not promote greater recombination of electrons and holes near the electrode interface are preferred. All antireflection layers known in the art and considered suitable for use in the present invention can be used. The preferred antireflection layer according to the present invention is silicon nitride, silicon oxide, aluminum oxide, titanium oxide or a mixture of at least two thereof and / or a combination of at least two layers thereof. According to a preferred embodiment, the antireflection layer is silicon nitride, i.e., Si x N y , especially when silicon wafers are used, wherein x is about 2-4 and y is about 3-5.
[0084] According to the present invention, one or more passivation layers can be applied to the substrate, preferably the front side and / or back side of the silicon wafer as the outer layer. The passivation layer can be applied before forming the front electrode or before applying the anti-reflection layer (if one of them exists). Preferably, the passivation layer is a passivation layer that reduces the electron / hole recombination rate near the electrode interface. Any passivation layer known in the art and considered to be applicable in the present invention can be used. According to the present invention, the passivation layer can be silicon nitride, aluminum oxide, silicon dioxide and titanium dioxide. According to the most preferred embodiment, aluminum oxide is used. Preferably, the passivation layer has a thickness of 0.1nm to 2μm, more preferably 1nm to 1μm, and most preferably 1nm to 200nm.
[0085] Besides the above-mentioned layers which directly contribute to the main functions of the solar cell, further layers can be added according to the invention for mechanical and chemical protection.
[0086] The battery can be encapsulated to provide chemical protection. Encapsulation is well known in the art and any encapsulation suitable for the present invention can be used. According to a preferred embodiment, a transparent polymer (commonly referred to as a transparent thermoplastic resin) is used as an encapsulation material, provided that such an encapsulation exists. Preferred transparent polymers herein are silicone rubber and polyethylene vinyl acetate (EVA).
[0087] A transparent glass sheet may also be added to the front side of the solar cell to provide mechanical protection thereto. Transparent glass sheets are well known in the art, and any transparent glass sheet suitable for use in the present invention may be employed.
[0088] A backside protection material may be added to the back side of the solar cell to provide mechanical protection. Backside protection materials are well known in the art and any backside protection material deemed suitable in the present invention may be used. A preferred backside protection material according to the present invention is a backside protection material having good mechanical properties and weather resistance. A preferred backside protection material according to the present invention is polyethylene terephthalate with a polyvinyl fluoride layer. It is preferred according to the present invention that the backside protection material is present below the encapsulation layer (in the case where a backside protection layer and encapsulation are present).
[0089] Frame materials may be added to the outside of the solar cell to impart mechanical support. Frame materials are well known in the art and any frame material deemed suitable for use in the present invention may be employed. A preferred frame structure according to the present invention is aluminum.
[0090] Technical Effects
[0091] The invention enhances the contact between the electrode and silicon and reduces the flow temperature by adding a specific amount of zinc oxide into a glass powder composition containing rare earth metal oxide.
[0092] Example
[0093] The following examples show the glass powder of the present invention, the silver-aluminum paste containing the glass powder, the preparation method of the N-type solar cell prepared from the silver-aluminum paste, and the performance of the product.
[0094] Preparation of glass powder, silver aluminum paste and solar cell substrate with electrodes
[0095] The glass powder was prepared by the following steps:
[0096] Weigh the components of the glass powder composition according to the ratio shown in Table 1 and combine them;
[0097] The combined mixture was loaded into an alumina crucible, placed in a muffle furnace and kept at 1100°C for 60 minutes;
[0098] The alumina crucible containing the molten glass was removed from the muffle furnace, and the molten glass was poured into a bucket containing deionized water for water quenching;
[0099] The water-quenched glass slag is ground into glass powder with D50=1.1-1.3 μm using a ball mill.
[0100] Prepare the silver aluminum paste by the following steps:
[0101] A mixture was prepared according to the following composition, mixed with a mixer, and then a three-roll mill was used to prepare a uniformly dispersed silver-aluminum paste:
[0102] Glass powder: 5 wt%;
[0103] Silver powder (D50: 2 μm): 85 wt%;
[0104] Aluminum powder (D50: 2 μm): 1.5 wt%;
[0105] Silicon powder (D50: 1 μm): 0.5 wt%;
[0106] Organic solvent: diethylene glycol butyl ether acetate, 5.6 wt%.
[0107] Resin: cellulose acetate butyrate, 0.6 wt%;
[0108] Organic dispersant: oleic acid, 0.6 wt%;
[0109] Thixotropic agent: hydrogenated castor oil, 0.6 wt%;
[0110] Lubricant: alkyl-modified silicone oil, 0.6 wt%.
[0111] The solar cell substrate with electrodes is prepared by the following steps:
[0112] Silver aluminum paste was screen printed onto an N-type silicon wafer of size 182 mm with a layer of aluminum oxide and a layer of silicon nitride passivation layer, and a solar cell substrate with electrodes was prepared by rapid sintering with a peak temperature of 750°C and a time of 16 seconds from room temperature to peak temperature.
[0113] Determination of Flow Temperature of Glass Powder
[0114] The flow temperature of the glass powder is determined as follows:
[0115] The glass powder is pressed into a cylinder with a diameter of 0.2 cm and a height of 0.5 cm by a mold, and then placed in a cavity with a starting temperature of 25°C, a heating rate of 10°C / min, and a final temperature of 800°C for heating. While heating, a camera is used to shoot a projected image from the side. The glass powder cylinder first softens under heating, then gradually spreads down, and finally flows flat on the substrate. The temperature corresponding to the leveling is the flow temperature.
[0116] Determination of glass transition temperature of glass powder
[0117] The glass transition temperature of glass powder is determined as follows:
[0118] NETZSCH- The DSC curve of the glass powder was measured using a STA449F3 differential scanning calorimeter from GmbH with a temperature program of a starting temperature of 25°C, a heating rate of 10°C / min, and a final temperature of 800°C, and then the glass transition temperature was obtained from the DSC curve.
[0119] Measurement of contact resistance between solar cell substrate and electrodes
[0120] The contact resistance between the solar cell substrate and the electrode is measured as follows:
[0121] The contact resistance between the solar cell substrate with electrodes and the electrodes was measured using a TLM-SCAN instrument commercially available from pv-tools GmbH, Lower Saxony, Germany, at 1.2 mm probe spacing, 0.5 mm tip radius.
[0122] Experimental data and analysis
[0123] The formulation of the glass frit composition, the flow temperature and glass transition temperature of the glass frit, and the measured values of the contact resistance Rc of the substrate with the electrode are summarized in Table 1.
[0124] It can be seen from Table 1 that when the content of zinc oxide in the glass powder composition is about 13 mol%, the glass powder flow temperature is high, and when the content of zinc oxide increases to 16 mol%, the glass powder flow temperature decreases significantly. Thereafter, as the content of zinc oxide continues to increase to about 20 mol%, the flow temperature gradually increases slightly.
[0125] Similarly, when the zinc oxide content in the glass frit composition is about 13 mol%, the contact resistance of the substrate with the electrode is high, and when the zinc oxide content increases to 16 mol%, the contact resistance decreases significantly. Thereafter, as the zinc oxide content continues to increase to 20 mol%, the contact resistance increases stepwise.
[0126] It can be seen that as the zinc oxide content increases, the flow temperature and contact resistance have optimal values, which appear when the zinc oxide content is in the range of 14-30 mol%, preferably 15-20 mol%, and more preferably 15-17 mol%. Obviously, when the zinc oxide content in the glass powder composition is within the above content range, a solar cell with better performance will be obtained.
[0127] Table 1
[0128]
Claims
1. A glass powder composition, wherein the glass powder composition comprises 14-30 mol %, preferably 15-20 mol %, more preferably 15-17 mol % of zinc oxide, and one or more of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate, based on the total amount of metal oxides in the glass powder composition.
2. The glass frit composition of claim 1, further comprising a rare earth metal oxide selected from the group consisting of lanthanum oxide, yttrium oxide, ytterbium oxide, scandium oxide, europium oxide, gadolinium oxide, and combinations thereof, preferably gadolinium oxide.
3. The glass powder composition of claim 2, wherein the content of the rare earth metal oxide in the glass powder composition is 1-10 mol %, preferably 1-5 mol %, and more preferably 1-3 mol %, based on the total amount of metal oxides in the glass powder composition.
4. The glass powder composition according to any one of claims 1 to 3, wherein the contents of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate in the glass powder composition are respectively lead oxide: 20-60 mol%, preferably 40-50 mol%, based on the total amount of metal oxides in the glass powder composition. Silicon oxide: 2-20 mol%, preferably 5-15 mol%, Boron oxide: 10-30 mol%, preferably 15-25 mol%, Aluminum oxide: 0-5 mol%, preferably 0.5-3 mol%, and / or Calcium carbonate: 1-10 mol %, preferably 2-8 mol %.
5. A glass powder obtained from the glass powder composition according to any one of claims 1 to 4, having a particle size D50 of 0.1-5 μm, preferably 0.2-3 μm, more preferably 0.5-2 μm.
6. A glass powder obtained from the glass powder composition of claim 5, having a glass transition temperature of 380-390°C.
7. A glass powder obtained from the glass powder composition according to claim 5 or 6, having a flow temperature of 540-570°C.
8. A silver-aluminum paste comprising the glass powder according to any one of claims 5 to 7.
9. The silver-aluminum paste of claim 8, wherein the content of the glass powder of any one of claims 5 to 7 is 2 to 15 wt %, preferably 2.2 to 10 wt %, and more preferably 2.5 to 8 wt %, based on the total amount of the silver-aluminum paste.
10. An N-type solar cell comprising an electrode prepared from the silver-aluminum paste of claim 8 or 9.
11. Use of zinc oxide for improving the contact between an N-type solar cell electrode and silicon, and / or improving the fluidity of a glass powder, wherein 14-30 mol %, preferably 15-20 mol %, more preferably 15-17 mol % of zinc oxide is added to a glass powder composition for preparing the glass powder, based on the total amount of metal oxides in the glass powder composition, the glass powder composition comprising one or more of lead oxide, silicon oxide, boron oxide, aluminum oxide and calcium carbonate, and the glass powder is contained in a silver aluminum paste for preparing the N-type solar cell electrode.
12. The use of claim 11, wherein the glass powder composition further comprises a rare earth metal oxide, the rare earth metal oxide being selected from lanthanum oxide, yttrium oxide, ytterbium oxide, scandium oxide, europium oxide, gadolinium oxide and combinations thereof, preferably gadolinium oxide; wherein the content of the rare earth metal oxide in the glass powder composition is preferably 1-10 mol %, more preferably 1-5 mol %, and most preferably 1-3 mol %, based on the total amount of metal oxides in the glass powder composition.
Citation Information
Patent Citations
Conductive paste for fine-line high-aspect-ratio screen printing in the manufacture of semiconductor devices
US20130180583A1
Electrode slurry that makes contact with p+ emitter of n-type solar cell
WO2022116646A1